2011
DOI: 10.1021/ja208390n
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis and Fcγ Receptor Binding of Homogeneous Glycoforms of Antibody Fc Domain. Presence of a Bisecting Sugar Moiety Enhances the Affinity of Fc to FcγIIIa Receptor

Abstract: Structurally well-defined IgG-Fc glycoforms are highly demanded for understanding the effects of glycosylation on antibody’s effector functions. We report in this paper chemoenzymatic synthesis and Fcγ receptor binding of an array of homogeneous IgG-Fc glycoforms. The chemoenzymatic approach consists of the chemical synthesis of defined N-glycan oxazolines as donor substratess, the expression of the Fc domain in a CHO cell line in the presence of an α-mannosidase inhibitor kifunensine, and an endoglycosidase-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 82 publications
2
114
0
Order By: Relevance
“…Thus, these Endo-S2-derived mutants represent the first glycosynthases that can efficiently transfer high-mannose and hybrid type N-glycans to core-fucosylated GlcNAc acceptor in an intact antibody. It should be mentioned that the Endo-A mutant (N171A and N171Q) could transfer high-mannose type N-glycan to the GlcNAc-Fc domain, but they were unable to use core-fucosylated GlcNAc-Fc as acceptor (22,23,36). These studies also show that the combined use of wild type Endo-S2 and Endo-S2 glycosynthase mutants provides a particularly efficient glycosylation remodeling approach to various homogeneous glycoforms of antibodies starting from a single precursor.…”
Section: Comparative Study On the Hydrolysis And Transglycosylationmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, these Endo-S2-derived mutants represent the first glycosynthases that can efficiently transfer high-mannose and hybrid type N-glycans to core-fucosylated GlcNAc acceptor in an intact antibody. It should be mentioned that the Endo-A mutant (N171A and N171Q) could transfer high-mannose type N-glycan to the GlcNAc-Fc domain, but they were unable to use core-fucosylated GlcNAc-Fc as acceptor (22,23,36). These studies also show that the combined use of wild type Endo-S2 and Endo-S2 glycosynthase mutants provides a particularly efficient glycosylation remodeling approach to various homogeneous glycoforms of antibodies starting from a single precursor.…”
Section: Comparative Study On the Hydrolysis And Transglycosylationmentioning
confidence: 73%
“…In parallel to the attempt to control glycosylation through host glycosylation pathway engineering (14 -20), a chemoenzymatic glycosylation remodeling method, which involves endoglycosidase-catalyzed deglycosylation and subsequent transglycosylation of intact antibodies, has been emerging as a promising approach to obtain homogeneous antibody glycoforms (21). We have initially shown that the Fc glycans of recombinant IgG-Fc domain could be remodeled through the enzymatic deglycosylation-transglycosylation steps under the catalysis of an appropriate endoglycosidase, including Endo-A 2 and Endo-D, without the need of denaturing the proteins (22)(23)(24). In 2012, we reported the first example of glycosylation remodeling of an intact therapeutic monoclonal antibody and intravenous immunoglobulin, which was enabled by the discovery of glycosynthase mutants of Endo-S, an endoglycosidase from Streptococcus pyogenes (25).…”
mentioning
confidence: 99%
“…During this study, it was discovered that the biantennary N-glycan structure with two terminal alpha-2,6-linked sialic acids is a common and optimal structure that is able to enhance the activities of antibodies against cancer, influenza, and inflammatory diseases. (22) and later applied to antibody glycoengineering (25)(26)(27). The strategy starts with the use of exoglycosidases or endoglycosidases to cleave most of the N-glycans to form a homogeneous glycoform containing a well-defined glycan, followed by extension of the glycan using glycosyltransfer enzymes.…”
Section: Significancementioning
confidence: 99%
“…Depending on the host cell line, the potential carbohydrate residues will have specific features such as bisecting GlcNAc residues or core fucosylation. Studies into the effect of bisecting structures present in antibody glycan moieties have shown that bisecting GlcNAc sugar residues lead to increased ADCC [33]. However, the presence (or absence) of other monosaccharides has been shown to have a more profound effect on in vivo modes of action.…”
Section: Antibody-dependent Cell-mediated Cytotoxicity (Adcc)mentioning
confidence: 99%
“…ERp57, calnexin/calreticulin, and/or protein disulfide isomerise) exhibited position effects in Productivity. Disulfide isomerase in particular increased specific mAb productivity by 55% in transient gene expression, but there were no/negative effects in stable gene expression [33]. In addition, targeting the unfolded protein response (UPR) pathway is another approach to enhancing recombinant protein yield.…”
Section: Experimental Strategies For Cell Line Modificationmentioning
confidence: 99%